2018
DOI: 10.1371/journal.pone.0196568
|View full text |Cite
|
Sign up to set email alerts
|

Rapid weight reduction does not impair athletic performance of Taekwondo athletes – A pilot study

Abstract: In combat sports such as taekwondo (TKD), athletes rapidly reduce body weight to achieve a desired weight category. Competition takes place 16–24 h after weigh-in and thus, the recovery time is an important factor for competition performance. The purpose of this study was to investigate the impact of rapid weight reduction (RWR) on athletic performance and associated hemorheological properties considering relevant recovery time. Five male TKD athletes reduced body weight by 5% within 3½ days. A simulated compe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
53
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(55 citation statements)
references
References 65 publications
0
53
1
Order By: Relevance
“…The results of laboratory-based trials investigating the effects of weight-cutting on varying aspects of exercise performance are also mixed. Indeed, there is research suggesting that weight-cutting practices negatively influence repeat-effort performance [9,10,13,17,37], while other research indicates no impact on repeat-effort [11,19,20], aerobic [14], and anaerobic performance [38]. It appears that when larger magnitudes (>3% body mass) are lost rapidly (<5 h) using thermal strain, high-intensity exercise performance is impaired [9,13,17].…”
Section: Weight-cutting and Performancementioning
confidence: 99%
See 2 more Smart Citations
“…The results of laboratory-based trials investigating the effects of weight-cutting on varying aspects of exercise performance are also mixed. Indeed, there is research suggesting that weight-cutting practices negatively influence repeat-effort performance [9,10,13,17,37], while other research indicates no impact on repeat-effort [11,19,20], aerobic [14], and anaerobic performance [38]. It appears that when larger magnitudes (>3% body mass) are lost rapidly (<5 h) using thermal strain, high-intensity exercise performance is impaired [9,13,17].…”
Section: Weight-cutting and Performancementioning
confidence: 99%
“…It appears that when larger magnitudes (>3% body mass) are lost rapidly (<5 h) using thermal strain, high-intensity exercise performance is impaired [9,13,17]. However, when a similar magnitude of weight is lost over multiple days (2–5) using a combination of methods (food restriction and body-fluid manipulation) laboratory-based trials have failed to observe any negative effect [11,19,20,38]. Studies that report a negative effect of weight-cutting on performance typically observe these effects on high-intensity repeat-effort performance, even up to 24 h following weight loss [9,13,17].…”
Section: Weight-cutting and Performancementioning
confidence: 99%
See 1 more Smart Citation
“…a difference of 5%; p < 0.05, Figure 3). In the only study that we identified in the literature in combat sports athletes subjected to RWL, that of Yang et al (2018) devoted to taekwondo, the authors note at the end of the series of fights (5 fights per series and a number of 3 series) values of: 179.6 ± 10.9 bpm at the end of the first series Advances in Physical Education (maximum: 193.3 ± 8.3 bpm), 176.8 ± 8.7 bpm in the second set (maximum:…”
Section: Discussionmentioning
confidence: 99%
“…The first limitation is the assessment of energy expenditure. It would have been desirable to separately determine the aerobic, anaerobic lactic and anaerobic alactic systems by the consumption of O 2 during a session, combined with measurements of maximum lactate concentration and the fast of excess oxygen uptake after exercise (EPOCFAST), as suggested by a recent study of Yang et al (2018). However, the implementation of these methods is proving difficult in the context of the poor technical facilities of our biological analysis laboratories.…”
Section: Discussionmentioning
confidence: 99%